How culture shapes the sexual and reproductive health practices among adolescent girls in Eastern Equatoria, South Sudan - Reajul Chowdhury; Kevin McKague (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2018)
Background: From 2011 to 2014, a programme aimed to improve sexual and reproductive health practices among adolescent girls was implemented by the non-governmental organization BRAC in partnership with the Government of South Sudan and with funding from the World Bank. The distinctive culture and norms in South Sudan offered unique challenges to the implementation of such a programme, which this study sought to explore. Objectives: This study investigated the sexual and reproductive health (SRH) behaviour of women and men in Eastern Equatoria State to identify the social norms and beliefs that affect communities' perception and behaviour regarding SRH issues. Methods: Data were gathered from seven key informant interviews and nine focus groups of adult women and men and adolescent girls and boys in Torit and Magwi Counties in Eastern Equatoria. Results: The study found a strong cultural preference for girls to demonstrate their fertility by beginning to have children at an early age (13-16 years) and to have many children (8-12). It also found that education on HIV/AIDS had been effective. Conclusions: To be effective in South Sudan, adolescent sexual and reproductive health programmes must take the current social norms and practices into account and learn from the successes of HIV/AIDS education programmes.